The Study on the Intention to Withdraw Lump-sum Social Insurance of Employees in Vietnam Based on the Theory of Planned Behavior (TPB) - Thi Huong Mai; Thi Mai Mai (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
Pensions play an important role in social security system of a nation. It helps reduce poverty among the elderly and ensures a decent standard of living after retirement. However, due to the impact of many economic and demographic variables, members of the system may leave the system earlier than supposed when they decide to have early retirement or lump-sum withdrawal of social insurance benefits before retirement age (Argento et al., 2015). There are many types of early retirement withdrawals such as hardship withdrawals, loans (withdrawals of a portion of your own retirement plan money, withdrawals, and transfers to another form of retirement accumulation. Motivations for early withdrawal may be different for each individual. In 2020, however, under the impact of the Covid-19 pandemic, lump-sum early retirement withdrawal becomes a more attractive option for individuals (Lee andHanna, 2020). Accordingly, this study aims to examine the factors affecting the intention to withdraw lump-sum social insurance benefits of employees through a survey of 250 participants that are currently in Vietnam, thereby providing policy recommendations to finalize legislation on social insurance and ensure the rights of workers.